Experimental study of defect formation during processing of randomly-oriented strand carbon/PEEK composites. (October 2015) - Landry, Benoit; Hubert, Pascal
Abstract: An investigation of the moulding defects formed during compression moulding of randomly-oriented strand carbon/PEEK composites is presented. The cause of defect formation was identified as non-uniform shrinkage due to a high coefficient of thermal expansion at the onset of crystallization. Panels with void content ranging from 0% to 1.3% were moulded by releasing the moulding pressure at specific temperatures during the cooling process. Mechanical tests showed a reduction in specimen compressive strength from 15% to 25% for a void content of 0.63–1.3%. It was concluded that the high concentration of porosity near the surface of the panels was the likely cause of the strength reduction.